Unscripted Joss Byrd - Peñaflor, Lygia Day (2016)
Joss Byrd, Americas most sought-after young actress, navigates the personal pressures of working on a new film and staying true to herself.
Keywords: Actresses -- Fiction; Self-actualization (Psychology) -- Fiction; Fiction